The Innovation of Tibo-Tibo Fisherwomen’s Business Development - Tinneke E.M. Sumual; Grace Jenny Soputan; Arie F. Kawulur (Journal of International Conference Proceedings (JICP), 2020)
This paper intends to description of conceptual model of business development innovation which will be applied to fisherwomen’s Tibo-Tibo business in North Minahasa Regency. This study utilises descriptive-qualitative method. Data collections were used focus group discussions (FGD) and observation. Data were analysed qualitatively. The results of the study exhibit that the business development innovation model consist of three categories namely local potentials product innovation (fresh fish), digital marketing innovation and direct marketing, as well as organizational innovation into culinary businesses and frozen food.